Analisis Fundamental Makro, Struktur Kepemilikan terhadap Nilai Perusahaan dengan Struktur Modal, Kinerja Keuangan, Karakteristik Perusahaan sebagai Variabel Interverning pada Perusahaan Sektor Makanan dan Minuman di BEI Tahun 2019-2023 - Rohmawati, Ade Putri Indri; Hwihanus (LANCAH: Jurnal Inovasi dan Tren, 2024)
In this study, firms in the food and baverages sector listed on the IDX between 2019 and 2023 will have their ownership structure, macrofundamentals, capital structure, financial performance, and company characteristics examined and evaluated as intervening variables on firm value. The investigation’s secondary data source is the company annual reportr. The study’s samples were thirty food and baverages enterprises that were listed on the IDX. The hypothesis was tested, and findings indicate that four independent variables significantly and favorably effect the dependent variable, firm value, whereas the remaining nine variables very slightly and negatively affect the dependent variable.